أزمة كوفيد 19 وأثرها الإقتصادية على النقل البحري في الجزائر حالة المحروقات - وئام عمار, وحيد بومدين ملوك (My University, 2022)
Maritime transport is one of the most used means in international trade, and the Corona pandemic has caused major disruptions in maritime activity. Shed light on the most important economic effects resulting from the Covid-19 crisis; One of the most difficult challenges in contemporary history across the global economy is the transportation of goods; in the world in general and in Algeria in particular; Although the pandemic is still present and has not yet disappeared, its vestiges are beginning to appear on the economy and its branches. The precautionary measures adopted by governments to deal with the epidemic by restricting the flow of international trade, the partial or total closure of factories, the disruption of the investment wheel and the temporary suspension of international trade relations; This had a negative impact on maritime transport and therefore the transport of hydrocarbons. In the end, we will try to make recommendations and suggestions for the advancement of the national economy as well as the sector of maritime transport of hydrocarbons
Keywords: Shipping, Corona Pandemic, Hyproc